2004
DOI: 10.1890/03-0629
|View full text |Cite
|
Sign up to set email alerts
|

Does Intraguild Predation Enhance Predator Performance? A Stoichiometric Perspective

Abstract: Ecological stoichiometry provides a novel context for elucidating the occurrence of intraguild predation. Recent data show that predators on average have a higher nitrogen content and lower C:N ratio than potential herbivorous prey. Thus, many predators may be nitrogen limited, and intraguild predation may allow them to increase their nitrogen intake and growth by supplementing a diet of herbivores with more nitrogen-rich intraguild prey. We tested this hypothesis using an assemblage of salt-marsh-inhabiting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 68 publications
3
76
1
1
Order By: Relevance
“…Consumer–resource nutrient ratios are typically used as indicators of the strength of consumer nutrient limitation (Filipiak & Weiner, 2017; Matsumura et al., 2004; Sterner & Elser, 2002). Here, we used the threshold elemental ratio (hereafter TER, Sterner & Elser, 2002; Urabe & Watanabe, 1992) to identify the point at which a consumer (i.e., spider) growth switches from limitation by one element to another.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumer–resource nutrient ratios are typically used as indicators of the strength of consumer nutrient limitation (Filipiak & Weiner, 2017; Matsumura et al., 2004; Sterner & Elser, 2002). Here, we used the threshold elemental ratio (hereafter TER, Sterner & Elser, 2002; Urabe & Watanabe, 1992) to identify the point at which a consumer (i.e., spider) growth switches from limitation by one element to another.…”
Section: Methodsmentioning
confidence: 99%
“…(2004), for example, the C:N TER in a predator–prey interaction is given by: TERC:N=false(C:N preyfalse/C:N predatorfalse)>normalαnormalN/normalαnormalCwhere C:N prey and C:N predator are the C:N in prey and predator biomass, and α N is the maximum gross growth efficiency for N (i.e., fraction of ingested N that the predator converts into new biomass), α C is the maximum gross growth efficiency for C (i.e., fraction of ingested C that the predator converts into new biomass). To calculate the TER for each spider, we used a gross growth efficiency α C  = 0.65 C and α N  = 0.70 (Fagan & Denno, 2004; Fagan et al., 2002; Matsumura et al., 2004; Wiesenborn, 2013), and two values for α PL  = 0.6 (low maximum gross growth efficiency; Lehman, 1993) and α PH (high maximum gross growth efficiency; DeMott, Gulati, & Siewertsen, 1998; Frost et al., 2006). Values for α N /α C  = 1.077, α PL /α C  = 0.923, α PH /α C  = 1.333, and α PL /α N  = 0.857, and α PH /α N  = 1.143.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7), they appear to have relatively inflexible diets that require them to also consume plant material (Jim enez et al 2012), and they may continue to eat high-quality plant tissue even when invertebrate prey are also available. Several studies have suggested (Denno & Fagan 2003;Matsumura et al 2004) that even a (2012) found that Orchelimum grew better on a mixed diet including both prey and plant material than on either single diet alone. We found that Orchelimum exhibited greater relative growth rates on plants with greater foliar nitrogen (Fig.…”
Section: W E a K O R A B S E N T T R O P H I C C A S C A D E Smentioning
confidence: 99%
“…Omnivory is therefore favoured by the relative scarcity of food items that are good stoichiometric matches to the consumer. Of course, the evolution of omnivory is not just about stoichiometry ( Matsumura et al , 2004 ). Diet mixing in general can dilute toxins in food, reduce the risk of predation or parasitism, and increase resistance to natural enemies ( Singer & Bernays, 2003 ).…”
Section: Introductionmentioning
confidence: 99%